Small hysteresis and giant magnetocaloric effect in Nb-substituted (Mn, Fe)2(P, Si) alloys. (November 2019) - Hu, Shuyuan; Miao, Xuefei; Liu, Jun; Ou, Zhiqiang; Cong, Mengqi; Haschuluu, Oimod; Gong, Yuanyuan; Qian, Fengjiao; You, Yurong; Zhang, Yujing; Xu, Feng; Brück, Ekkes
Abstract: The influence of Nb substitution on the structure, magnetoelastic transition and magnetocaloric properties has been investigated for the Mn1.1 Fe0.85- x Nb x P0.43 Si0.57 alloys. The substitution for Fe by merely 4.7 at.% Nb (i.e. x  = 0.04) significantly diminishes the thermal hysteresis from 10 to 1 K due to the reduced structural discontinuity crossing the magnetoelastic transition. This also improves the mechanical stability. The Curie temperature of the magnetoelastic transition is lowered by approximately 11.6 K per at.% of the Nb substitution, originating from the enhanced covalent bonding that favors the paramagnetic state. The giant magnetocaloric effect is still retained in the Nb-substituted alloys. Graphical abstract: Image 1 Highlights: A small thermal hysteresis of 1 K was obtained in Nb-substituted Mn–Fe–P–Si alloys. Giant magnetocaloric effect was retained in the Nb-substituted Mn–Fe–P–Si alloys. Curie temperature can be effectively tuned by 11.6 K per at.% of Nb substitution.